2009
DOI: 10.3892/ijo_00000513
|View full text |Cite
|
Sign up to set email alerts
|

An 8-gene signature, including methylated and down-regulated glutathione peroxidase 3, of gastric cancer

Abstract: Abstract.We have identified an 8-gene signature with significant expression differences between gastric cancer and normal gastric tissues. This 8-gene set can predict the normal and cancer status of gastric tissues with more than 96% accuracy in a totally independent microarray dataset. The 8 genes are composed of down-regulated KLF4, GPX3, SST and LIPF, together with up-regulated SERPINH1, THY1 and INHBA in gastric cancer. To corroborate the differential gene expression pattern, we chose GPX3 and examined its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In this study, we found that HSP47 mRNA and protein expression were highly upregulated in various GC cell lines and many human GC tissues. Similarly, previous studies have shown that HSP47 expression was upregulated in GC tissues [ 12 , 20 ], and HSP47 was also detected in scirrhous GC by immunohistochemical analysis [ 21 ].…”
Section: Discussionsupporting
confidence: 67%
“…In this study, we found that HSP47 mRNA and protein expression were highly upregulated in various GC cell lines and many human GC tissues. Similarly, previous studies have shown that HSP47 expression was upregulated in GC tissues [ 12 , 20 ], and HSP47 was also detected in scirrhous GC by immunohistochemical analysis [ 21 ].…”
Section: Discussionsupporting
confidence: 67%
“…Finally, great of relevance, we found an upregulation of Matrix Metalloproteinase family (MMP1, MMP3, MMP10, MMP12), that are overexpressed in gastric cancer as a result of NF-Kb activation thus promoting migration and invasion, and are associated with poor prognosis (37)(38)(39)(40). Among most downregulated genes we found GPX3, PTGER3 and LIPF (−47.5 and −435.63 of fold change for Diffuse and Intestinal tumors respectively), that resulted hypermethylated in gastric cancer (41,42).…”
Section: Patientsmentioning
confidence: 68%
“…Zhang et al. reported that the SERPINH1 gene is upregulated in gastric cancer and can be used as a gastric cancer biomarker [18] . In lung adenocarcinoma, high SERPINH1 expression predicts poor prognosis [19] .…”
Section: Discussionmentioning
confidence: 99%